The relationship between Meconium stained amniotic fluid and early neonatal sepsis. - Dayoub, Adnan; Othman, Moneer; Nezha, Bana (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: Meconium stained amniotic fluid can either occur as a physiologic event due to increasing gestational age or it may be pathological, indicating fetal distress, and because of the prevalence of early neonatal sepsis and the risk of late diagnosis, the study aims at determining the prevalence of early neonatal sepsis with amniocentesis, determining the risk factors for amniotic fluid suspension, and the possible association between these predisposing factors and early bacterial neonatal sepsis . Patients and methods: 46 neonates with meconium stained amniotic fluid were investigated for sepsis and dividing them into two groups according to the presence or absence of risk factors and studying the association of sepsis with these factors. Results :There was a strong positive correlation between the presence of possible fetal factors for the occurrence of congenital infection and early neonatal sepsis, a moderately strong relationship between the presence of parental factors to meconium stained amniotic fluid and early neonatal sepsis. Conclusions: The prevalence of amniocentesis in neonates is associated with the presence of potential fetal and parental factors for amniocentesis and early neonatal sepsis المقدمة : يحدث تعقي السائل الأمنيوسي ( Meconium stained amniotic fluid) بشكل فيزيولوجي عند زيادة العمر الحملي أو يكون مؤشراً على وجود الشدة حول الولادة ، وبسبب انتشار الإنتان الباكر عند الوليد (Early neonatal sepsis) وما يترتب عليه من مخاطر بسبب التأخر في التشخيص ، تهدف الدراسة إلى تحديد نسبة شيوع الإنتان الباكر لدى الولدان مع حالة تعقي سائل أمنيوسي ، تحديد عوامل الخطورة المؤهبة لتعقي السائل الأمنيوسي وإمكانية وجود ارتباط بين هذه العوامل المؤهبة وبين الإنتان الجرثومي الباكر عند الوليد . المواد والطرائق : 46 وليداً مع حالة تعقي سائل أمنيوسي تم تحري وجود الإنتان عندهم وتقسيمهم إلى مجموعتين وفقاً لوجود أو غياب عوامل الخطورة ودراسة ارتباط حدوث الإنتان مع تلك العوامل . النتائج : نسبة انتشار الإنتان عند ولدان تعقي السائل الأمنيوسي كانت 32.6% ، هناك علاقة طردية قوية بين وجود العوامل الجنينية المحتملة لحدوث التعقي وبين حدوث الإنتان الباكر عند الوليد ، علاقة متوسطة القوة بين وجود العوامل الوالدية لتعقي السائل الأمنيوسي وبين حدوث الإنتان الباكر عند الوليد . الاستنتاجات : شيوع تعقي السائل الأمنيوسي لدى حديثي الولادة ، هناك ارتباط بين وجود العوامل الجنينية والوالدية المحتملة لحدوث تعقي السائل الأمنيوسي وبين حدوث الإنتان الوليدي الباكر .